A Control Chart for COM–Poisson Distribution Using Resampling and Exponentially Weighted Moving Average. (3rd March 2015) - Aslam, Muhammad; Azam, Muhammad; Jun, Chi‐Hyuck
Abstract : In this paper, we propose a control chart using exponentially weighted moving average (EWMA) statistic for count data based on the Conway–Maxwell–Poisson (called COM–Poisson) distribution. Repetitive sampling is considered by constructing two pairs of control limits for the proposed control chart. The performance of the proposed control chart is evaluated using the average run length (ARL) for various values of specified parameters. It has been observed that the proposed control chart is more efficient in terms of ARLs as compared to the existing control charts. The tables are provided and explained with the help of example. Copyright © 2015 John Wiley & Sons, Ltd.